2020
DOI: 10.17341/gazimmfd.490516
|View full text |Cite
|
Sign up to set email alerts
|

Farklı yük şartlarında kömür yakıtlı termik güç santrallerinin termodinamik analizi

Abstract:  Energy and exergy efficiencies of the thermal power plant  The effects of steam parameters on the performance  The maximum exergy loss occurs in the thermal power plantIn this study, the thermodynamic analysis of the sub-critical and super-critical coal-fired power plants under various load conditions have been investigated. Figure A. Schematic diagram of the optimized coal-fired power plant Purpose: The aim of this study is to show the effect of live steam parameters on thermal and exergy efficiencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…When the energy and exergy efficiencies of Case 4 and the Reference Power Plant are compared, the energy efficiency increased by 9.24 % and the exergy efficiency increased by 8.06% under 100% loading conditions. As a result of this study, it has been shown that steam conditions under different loadings have a significant effect on the first and second laws efficiency of the systems [18]. Acır and others [19], first and second law analyses were made for a 160 MW TPP.…”
Section: Introductionmentioning
confidence: 95%
“…When the energy and exergy efficiencies of Case 4 and the Reference Power Plant are compared, the energy efficiency increased by 9.24 % and the exergy efficiency increased by 8.06% under 100% loading conditions. As a result of this study, it has been shown that steam conditions under different loadings have a significant effect on the first and second laws efficiency of the systems [18]. Acır and others [19], first and second law analyses were made for a 160 MW TPP.…”
Section: Introductionmentioning
confidence: 95%